2019
DOI: 10.1111/jora.12437
|View full text |Cite
|
Sign up to set email alerts
|

Belief in a Loving Versus Punitive God and Behavior

Abstract: We examined the extent to which beliefs in a loving God and punitive God correspond with self‐reported behavior in an online, longitudinal survey involving three waves of data collection, each separated by 6 months. Adolescents (N = 760) reported the extent to which they believed in a loving God and a punitive God (Times 1 and 3) and reported their engagement in benevolent (helping and forgiveness) and aggressive behavior (Times 2 and 3). Participants strongly endorsed a loving God but not a punitive God. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Autonomously held values are likely to be more strongly related to identity and behavior (Knafo & Assor, ). More recently, Shepperd et al () found that belief in a punitive God—whom they likened to an authoritarian parent—was associated with more aggressive and less helpful behavior among adolescents. Measuring pro‐social behavior is not equivalent to measuring values, however (Bardi & Schwartz, ).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…Autonomously held values are likely to be more strongly related to identity and behavior (Knafo & Assor, ). More recently, Shepperd et al () found that belief in a punitive God—whom they likened to an authoritarian parent—was associated with more aggressive and less helpful behavior among adolescents. Measuring pro‐social behavior is not equivalent to measuring values, however (Bardi & Schwartz, ).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…Research finds that individuals who believe in a benevolent God (i.e. loving and kind) are more helpful and forgiving (Shepperd et al , 2019) and are less likely to act aggressively (Johnson et al , 2013) than individuals that believe in a punitive God (i.e. vindictive and angry).…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Experimental studies that prime a punitive God provide no clear evidence that a belief in an omniscient being that punishes wrongdoers corresponds with less risk behavior (for a review, see Shepperd et al, 2019). Moreover, longitudinal research reveals that belief in a punitive God corresponds with reports of more aggression six and 12 months later (Shepperd et al, 2019). In contrast, this same research reveals strong support that belief in a loving God corresponds with less risk behavior.…”
Section: Religions Promote a Watching Judging Omniscient Entitymentioning
confidence: 99%